Modelling Regional Networks and Local Adaptation: West-Central Sicilian Relief Louteria - Andrew Farinholt Ward (Les Carnets de l’ACoSt)
The consumption and adaptation of Greek material culture by non-Greek peoples in ancient western Sicily, and the wider Mediterranean, has been an ongoing point of contention in scholarship: do Greek objects influence the peoples that use them, and by their movement and trade are these objects and their figured surfaces active agents of Hellenization? Acknowledging that framing future discussion through postcolonialism only perpetuates the anachronistic colonialist model, this dissertation applies the materialist theory of transculturality to an understudied class of terracotta objects distributed and adapted through Ancient Sicily: louteria, arulae, and other ritual furniture impressed with cylinder-roll matrices. This announcement summarizes the results of an interdisciplinary methodology combining technical and iconographic analyses of the stamp series, reconstruction of the then-stamped terracottas’ contexts, and spatial and statistical modelling of their distribution patterns. This holistic approach to material study reveals a highly complex network of exchange, adaptation, and local production in sixth and fifth century Sicily far more dynamic than the simple binary of colonizer and colonized.